2018
DOI: 10.1186/s13287-018-0919-9
|View full text |Cite
|
Sign up to set email alerts
|

Co-culturing nucleus pulposus mesenchymal stem cells with notochordal cell-rich nucleus pulposus explants attenuates tumor necrosis factor-α-induced senescence

Abstract: BackgroundCell therapy for the treatment of intervertebral disc degeneration (IDD) faces serious barriers since tissue-specific adult cells such as nucleus pulposus cells (NPCs) have limited proliferative ability and poor regenerative potential; in addition, it is difficult for exogenous adult stem cells to survive the harsh environment of the degenerated intervertebral disc. Endogenous repair by nucleus pulposus mesenchymal stem cells (NPMSCs) has recently shown promising regenerative potential for the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Some studies have showed that inflammatory cytokines induce cell senescence in some cell types, including endothelial progenitor cells and osteoarthritic osteoblasts [14,15]. Importantly, inflammatory cytokines often induces disc NP cell senescence in previous researches [16–18]. Therefore, we deduce that inflammation response-mediated disc NP cell senescence plays an important role in accelerating disc degeneration.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Some studies have showed that inflammatory cytokines induce cell senescence in some cell types, including endothelial progenitor cells and osteoarthritic osteoblasts [14,15]. Importantly, inflammatory cytokines often induces disc NP cell senescence in previous researches [16–18]. Therefore, we deduce that inflammation response-mediated disc NP cell senescence plays an important role in accelerating disc degeneration.…”
Section: Introductionmentioning
confidence: 63%
“…Inflammation response and cellular senescence are two classical features during disc degeneration [5–13]. Furthermore, there is a positive relationship between inflammation response and disc cell senescence [16–18]. Therefore, inhibition of inflammation response-induced disc cell senescence may be helpful to retard disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…IDD disrupts the distribution and density of the aged bone tissues in vertebrae ( 2 ). Nucleus pulposus (NP) mesenchymal stem cells (MSCs) can promote the regeneration of intervertebral discs due to their endogenous repair function ( 3 ). Furthermore, since a loss of NP cells and the ECM are the primary causes of IDD, and MSC differentiation is conducive to intervertebral disc regeneration, the ability of NPMSCs to form cartilage can help to protect patients with IDD ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pcDNA-SOX9 markedly promotes the synthesis of extracellular matrix, inhibits levels of IL-6 and TNFa and apoptosis of chondrocytes. SOX9, like Col II and aggrecan, is a member of extracellular matrix-related genes (38). Inflammatory cytokines maintain the balance between the synthesis and catabolism of extracellular matrix proteins (29).…”
Section: Discussionmentioning
confidence: 99%